2009
DOI: 10.1021/ma900351r
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Single Homopolymer Chain in Microphase-Separated Block Copolymer Monolayer Studied by Scanning Near-Field Optical Microscopy

Abstract: The phase-separated structure of poly(isobutyl methacrylate)-block-poly(octadecyl methacrylate) (PiBMA-b-PODMA) monolayer and single poly(isobutyl methacrylate) (PiBMA) chain dispersed therein were investigated by scanning near-field optical microscopy (SNOM), which enabled us to observe with high spatial resolution beyond the diffraction limit of light. The conformation of the individual homo-PiBMA chains was quantitatively evaluated from the fluorescence intensity distribution. We found that the homo-PiBMA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…An outstanding question related to the volume-asymmetry mechanism is whether the selective partitioning of the homopolymers to the larger particles can be observed experimentally. There is a body of prior work on combining small-angle X-ray scattering and small-angle neutron scattering to identify the locations of homopolymers in block-polymer microstructures (42,43), and microscopy has also been employed for this purpose (44). The small domain sizes of the particles in these phases and the subtle (but important) differences in A-polymer volume fractions within different particles pose nontrivial experimental obstacles, but it may be possible to observe the partitioning effect through changes in the relative intensity of the scattering from the Z16 particles in C15 relative to the Z12 particles as the homopolymer volume fraction increases.…”
Section: Discussionmentioning
confidence: 99%
“…An outstanding question related to the volume-asymmetry mechanism is whether the selective partitioning of the homopolymers to the larger particles can be observed experimentally. There is a body of prior work on combining small-angle X-ray scattering and small-angle neutron scattering to identify the locations of homopolymers in block-polymer microstructures (42,43), and microscopy has also been employed for this purpose (44). The small domain sizes of the particles in these phases and the subtle (but important) differences in A-polymer volume fractions within different particles pose nontrivial experimental obstacles, but it may be possible to observe the partitioning effect through changes in the relative intensity of the scattering from the Z16 particles in C15 relative to the Z12 particles as the homopolymer volume fraction increases.…”
Section: Discussionmentioning
confidence: 99%
“…SNOM was successfully applied to study conformations of single dye-labelled poly(isobutylmethacrylate) chains in dense films. [327][328][329] For homogeneous LB monolayers strong segregation of polymer chains was detected with the value of n $ 1=2. [327] SFM was applied to study the conformation of individual comb-like macromolecules surrounded by a dense Langmuir monolayer with the polymer chains of the same nature as the side chains.…”
Section: First Steps Towards Molecular Walkermentioning
confidence: 99%
“…Because the packing frustration arises from deviation in the chains from their preferred conformation, scientists plan to devise methods to visualize the chain conformation not only in bulk [116][117][118][119][120][121] but also in restricted dimensions. [122][123][124] Small-angle neutron (or X-ray) scattering has been used to evaluate the gyration radius R g of the subchains in lamellar-forming block copolymers. [116][117][118][119] The results of these evaluations have shown that the lateral interpenetration of the subchains is smaller than the interpenetration normal to the interface.…”
Section: Some Examples and Perspective Of Polymer Nanostructure Studimentioning
confidence: 99%